EAP needs analysis in higher education: Significance and future direction - Soo, Ruey Shing; S. S., Tam (2011)
This paper is prompted by the growth and demand for English for Academic Purposes (EAP) which has increased immensely in the global higher education sector. It provides an overview of some issues pertaining to the conduct of EAP needs analysis in ESL and EFL contexts. This paper consists of four sections. The first section tries to review the development, description and categorization of EAP. The second discusses the different situations in which EAP courses are conducted according to the status of the English language in respective countries. The third focuses on the most essential issue in EAP, that is, the content or curriculum of EAP courses. The paper concludes by looking at the rationale and focus of conducting needs analysis at the tertiary level.